2001
DOI: 10.1038/35102160
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells find their niche

Abstract: The concept that stem cells are controlled by particular microenvironments known as 'niches' has been widely invoked. But niches have remained largely a theoretical construct because of the difficulty of identifying and manipulating individual stem cells and their surroundings. Technical advances now make it possible to characterize small zones that maintain and control stem cell activity in several organs, including gonads, skin and gut. These studies are beginning to unify our understanding of stem cell regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
924
0
29

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,288 publications
(966 citation statements)
references
References 80 publications
13
924
0
29
Order By: Relevance
“…Signaling pathways such as Wnt, Notch, Janus kinase-signal transducer and activator of transcription (JAK-STAT), bone morphogenetic protein, Activin/ transforming growth factor␤/Nodal, and hedgehog interact to maintain stemness or to influence the developmental fate of stem cells within the niche. [40][41][42] In a previous study, the relevance of ␤-catenin-dependent Wnt signaling for sustaining quiescent HSCs was already demonstrated. 11 In a search of the origin of canonical Wnt ligands among cells of the stellate cell niche, liver parenchymal cells were identified as an important source.…”
Section: Discussionmentioning
confidence: 94%
“…Signaling pathways such as Wnt, Notch, Janus kinase-signal transducer and activator of transcription (JAK-STAT), bone morphogenetic protein, Activin/ transforming growth factor␤/Nodal, and hedgehog interact to maintain stemness or to influence the developmental fate of stem cells within the niche. [40][41][42] In a previous study, the relevance of ␤-catenin-dependent Wnt signaling for sustaining quiescent HSCs was already demonstrated. 11 In a search of the origin of canonical Wnt ligands among cells of the stellate cell niche, liver parenchymal cells were identified as an important source.…”
Section: Discussionmentioning
confidence: 94%
“…Stem cells, as well as multipotent progenitor cells and germ cells, reside in complex microenvironments or "niches" 52 . Several studies have revealed that O 2 levels might profoundly influence stem cell niches, and can promote the differentiation of certain types stem or progenitor cells, while inhibiting the differentiation of others.…”
Section: O 2 Levels Influence Stem Cell Phenotypesmentioning
confidence: 99%
“…It has been shown that the stem cell niche in normal adult tissues plays an essential role in maintaining stem cells as well as preventing tumorigenesis by providing inhibitory signals for proliferation and differentiation. On the other hand, it provides stimulatory signals for stem cell proliferation when tissue regeneration is needed [14]. The balance between inhibitory and stimulatory signals is the key for regulation of the balance between stem cell maintenance and tissue regeneration [15].…”
Section: Cancer Stem Cells-past and Currentmentioning
confidence: 99%